Kesetaraan Gender dan Politik: Studi Kasus Terpilihnya Julia Gillard dalam Lembaga Pemerintah Australia - Ummah, Aniqotul; Kristyafajar , Canza Anadya Sabrina Putri; Dewi, Nirina Jelita; Sarasvati, Raihana Devi (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2023)
This article explores the issue of gender equality in politics, with a focus on the case study of Julia Gillard's election as Australia's first Prime Minister in a particular year (election year). Julia Gillard plays an important role as the first woman to hold the highest office in Australia's government. Her election marked a milestone in efforts to increase women's participation in politics in the country. This research aims to analyze the factors that influenced Julia Gillard's election as Prime Minister, including the challenges she faced and strategies she used to achieve this position. Qualitative research methods were used to collect data through document analysis, interviews with relevant stakeholders, and literature review. The results showed that Julia Gillard's election was inseparable from her struggle and hard work when facing various political challenges. She overcame the stereotypical perceptions of women in politics and proved her competence in leading the country. In addition, support from her political party, fellow politicians, and the public also played an important role in achieving her election. In addition, this article reviews the impact of Julia Gillard's election as Prime Minister of Australia in promoting gender equality and change in politics. Her leadership and policies during her tenure were also explained to understand the role of her contribution in realizing gender equality at the government level. By analyzing the case study of Julia Gillard, this journal seeks to provide insight into the importance of women's representation in politics and how the influence of her election can affect overall gender equality. This case study can provide guidance for other countries in their efforts to increase women's participation and representation in governmental institutions.